Perilaku Agresif di Jalan Raya: Analisis Literatur tentang Ekspresi Emosi, Stres, dan Norma Sosial di Kalangan Pengendara di Indonesia - Hafizhatul ‘Afifah; Neviyarni S (PT. Hasba Edukasi Mandiri, 2025)
Aggressive behavior on the road has become increasingly prevalent in Indonesia, particularly in urban areas characterized by high traffic density. Aggressive driving, commonly referred to as road rage, not only threatens traffic safety but also reflects broader psychological, environmental, and socio-cultural dynamics. This article aims to provide a narrative review of studies examining aggressive driving behavior within the Indonesian context. A narrative literature review approach was employed by analyzing relevant national and international scholarly articles published between 2015 and 2024. The literature was thematically analyzed to identify psychological factors, situational and environmental stressors, socio-cultural influences, as well as the impacts and preventive efforts related to aggressive driving. The findings indicate that aggressive road behavior emerges from the interaction of anger, frustration, low self-control, traffic-related stress, and social norms that legitimize dominance and confrontation. Such behaviors contribute to increased accident risk, interpersonal conflict, and a reduced sense of public safety. Therefore, comprehensive interventions integrating law enforcement, emotional regulation education, and the promotion of empathetic and prosocial driving culture are essential to mitigate aggressive behavior on the road.